Proceedings of 5th the International Conference on Operations Research and Enterprise Systems 2016
DOI: 10.5220/0005757503300339
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Integer Programming with Decomposition for Workforce Scheduling and Routing with Time-dependent Activities Constraints

Abstract: We present a mixed integer programming decomposition approach to tackle workforce scheduling and routing problems (WSRP) that involve time-dependent activities constraints. The proposed method is called repeated decomposition with conflict repair (RDCR) and it consists of repeatedly applying a phase of problem decomposition and sub-problem solving, followed by a phase dedicated to conflict repair. Five types of timedependent activities constraints are considered: overlapping, synchronisation, minimum differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2
1
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
(24 reference statements)
0
4
0
Order By: Relevance
“…That study revealed that tackling instances with 50 activities or more required considerable computational time. Hence, a greedy heuristic tailored for such scenarios with connected activities was proposed in [9] and an MIP with decomposition method was proposed in [10]. That decomposition method splits each problem into subproblems and solves each sub-problem with an MIP solver.…”
Section: Related Workmentioning
confidence: 99%
“…That study revealed that tackling instances with 50 activities or more required considerable computational time. Hence, a greedy heuristic tailored for such scenarios with connected activities was proposed in [9] and an MIP with decomposition method was proposed in [10]. That decomposition method splits each problem into subproblems and solves each sub-problem with an MIP solver.…”
Section: Related Workmentioning
confidence: 99%
“…Nevertheless, the boundary between these two categories is not always clearly defined and, for example, some studies addressing HHC problems do not consider coordination constraints (Bertels and Fahle, 2006), (Maenhout and Vanhoucke, 2009), (Chahed et al, 2009) while other articles take coordination constraints into account (Blais et al, 2003), (Eveborn et al, 2006), (Bachouch et al, 2011). Similar remarks hold for the WSRP without coordination constraints in (Castillo et al, 2009), (Goel and Meisel, 2013), (Laesanklang et al, 2015), , (Laesanklang and Landa-Silva, 2017) and (Algethami et al, 2018) and with coordination constraints in (Laesanklang et al, 2016). Let us note that Vehicle Routing Problems (VRP) or VRP with Time-Windows (VRPTW) are commonly studied without coordination constraints, but recent studies include theses considerations, (Drexl, 2012) presents a survey of VRP with theses constraints and their applications.…”
Section: The Context Of Scheduling and Routing Problems With Coordination Servicesmentioning
confidence: 88%
“…A clustering based approach referred to as Geographical Decomposition with Conflict Avoidance (GDCA) that splits the problem into sub-problems which consider geographical considerations and workers not performing a trip is proposed by (Laesanklang et al, 2015). The approach is extended by (Laesanklang et al, 2016) to Repeated Decomposition with Conflict Repair (RDCR) where all workers are available during the resolution of each sub-problem and may create conflicts (a worker is assigned to several trips) which are iteratively addressed. GDCA and RDCR are sub-problem resolution order dependent.…”
Section: The Context Of Scheduling and Routing Problems With Coordination Servicesmentioning
confidence: 99%
“…For a single-period model, the problem focuses on finding an integrated routing and scheduling plan. The plan must respect constraints related to patient visiting time window, minimum worker requirements, worker skill qualifications, and patient visit time window [4,5]. The objective function for a single-period model includes operation costs, travel distances, worker active times, preferences, etc.…”
Section: Introductionmentioning
confidence: 99%